A prospective evaluation of psycho-oncological factors on cancer outcomes / Caryn Chan Mei Hsien - Caryn, Chan Mei Hsien (2015)
This study examined the association between patient-physician fit, psychological distress and psychiatric morbidity on cancer outcomes. In this prospective single centre study, a total of 467 consecutively recruited adult oncology patients completed a battery of self-reported and objective assessments at four time points: within a month of diagnosis (baseline), and then 4-6 weeks, 6 months and 12-18 months after the first assessment. Questionnaires used included the Patient-Practitioner Orientation Scale (PPOS), Hospital Anxiety and Depression Scale (HADS), Patient Satisfaction Questionnaire (PSQ) and Job Satisfaction Scale (JSS). Psychiatric diagnoses were assessed using the Structured Clinical Interview for DSM-IV-TR (SCID). Physicians and nurses also formed part of the sample. Cancer patients and their oncologists were found to be patient-centred. Even when compared to physicians from three other specialties, oncologists were found to be the most patient-centred in terms of role orientation. There was a discrepancy in terms of performance status when rated by cancer patients and their own oncologists. Patient satisfaction was high despite a high level of psychological distress in both cancer patients and their oncologists. The level of treatment default (refusers, delayers, and non-completers of treatment) was also high, and was linked to psychiatric disorders and survival in this sample. Findings from this study contribute to the development of an important area of research through strengthening of what is known in the area of psycho-oncology by offering further insight and understanding of psychosocial factors and its subsequent outcomes in cancer.